PENGARUH METODE TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Novita Dwi Astuti (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
The research purpose to see influence method about achievement in mathematics consideration of self-regulated learning. The research method used in this an experimental method with design used is treatment by level 2x2. Hypotheses were tested using two way of variance ANOVA. The Research concluded that: (1) achievement in mathematics of study used cooperative learning method is higher than conventional teaching used lecturing method; (2) be found effect interaction between learning method and self-regulated learning about achievement in mathematics; (3) achievement in mathematics have to high self-regulated learning and study used cooperative learning method higher than conventional teaching used lecturing method; and (4) achievement in mathematics have to low self-regulated learning and study used cooperative learning method lower than conventional teaching used lecturing method. The teachers are hoped to use method which is related to material and self-regulated learning.